The jurisprudence of the Spanish Supreme Court is clear: requesting the renewal of the Spanish passport at the spanish consulate is indicative of the will to conservate the spanish nationality (notes to the Judgment of the Supreme Court of June 1, 2020) - Heredia Sánchez, Lerdys S. (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
This paper analyzes the Spanish Supreme Court Judgment of June 1, 2020, which resolves an appeal in cassation based on the application of Article 24.3 of the Civil Code regarding the cause of loss of Spanish nationality for those born abroad to a Spanish parent who was also born outside of Spain, due to the lack of a declaration of retention of Spanish nationality. This ruling is in line with its predecessor, the one issued by the Supreme Court on December 19, 2019, which has opened the way foravoiding the loss of nationality to Spaniards born abroad, since it is understood that by merely applying for a passport renewal, the provisions of our Civil Code are complied with.
Keywords: lost of nationality; Spanish nationality; passport renewal; Spanish Supreme Court Judgment